Inconsistent ENSO teleconnections over East Asia in early and late winter: role of Siberian land-atmosphere coupling - Xiadong An; Wen Chen; Tianjiao Ma; Lifang Sheng (Environmental Research Letters)
The El Niño–Southern Oscillation (ENSO) teleconnections over East Asia display inconsistency between early and late winter, yet the undering physical mechanisms remain unclear. Employing causal inference analysis, including Liang-Kleeman information flow and PC-MCI causal discovery, our study reveals a stable information flow from ENSO to the upper tropospheric atmospheric circulation (250 hPa) over southern East Asia. Building on this, we explore the reason behind the differences in ENSO teleconnections during early and late winter. Findings indicate that Siberian snow water equivalent acts as a ‘land bridge’, storing ENSO signals from early to late winter, which are then released via an ‘atmospheric bridge’ in late winter. Specifically, reduced snow water equivalent from early to late winter facilitates lower surface temperatures in late winter, serving as a cooling source to initiate an ENSO-related wave train over Eurasia. This leads to an inconsistent ENSO teleconnection in late winter, contrasting with early winter, and vice versa.